Hubungan Kemandirian Belajar dan Motivasi Berprestasi dengan Hasil Belajar Siswa - Imroatul Fitriana; Nyoman Sridana; Wahidaturrahmi Wahidaturrahmi; Sripatmi Sripatmi (Pendidikan Matematika FKIP Universitas Mataram, 2022)
Learning independence and achievement motivation are factors that can affect learning outcomes. However, there is a discrepancy between learning independence and achievement motivation with the learning outcomes obtained, so it is necessary to conduct research on this matter. This study aims to determine the relationship between learning independence and achievement motivation with student learning outcomes. This research is quantitative research with a population of 278 students with a sample of 38 students. The sampling technique used cluster random sampling. Collecting data using a questionnaire instrument and test questions. Data analysis techniques in the form of descriptive statistics and inferential statistics. The results of the study 1) there is a relationship between learning independence and learning outcomes of 0.182 with a weak level of relationship 2) there is a relationship between achievement motivation and learning outcomes of 0.327 with a moderate level of relationship 3) there is a relationship between learning independence and achievement motivation of 0.724 with a relationship level which is very strong 4) there is a significant relationship between learning independence and achievement motivation with the learning outcomes (0.333 score) with a moderate correlation.